COMPARATIVE RESEARCH OF ENALAPRIL AND ATENOLOL ANTIHYPERTENSIVE EFFICACY IN HIGH RISK PATIENTS - O. M. Moiseeva; S. V. Villevalde; I. V. Emelyanov; T. G. Ivanova (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the effecacy of enalapril (Enam, Dr.Reddy’s, India) and atenolol (Tenormin, AstraZeneca, UK) and their influence on processes of cardiovascular system remodeling in comparative research in patients with arterial hypertension. Material and methods. 38 patients with arterial hypertension stage II were examined. 21 patients were treated with enalapril (10-40 mg\d) and 17 – with atenolol (50-100 mg\d). Duration of therapy was 24 weeks.  A daily monitoring of blood pressure and echocardiography were made before and after the treatment. Spontaneous erythrocyte aggregation and deformability, spontaneous platelet aggregation and adhesive property of neutrophils were also estimated. A number of leucocytes carrying activation markers and expressing adhesive molecules was calculated. The plasma concentration of adhesive molecules (ICAM-1) and von Willebrand protein as well as serum concentration of N-terminal peptide of procollagen type III was also estimated. Results. Enalapril versus atenolol improved blood rheology, reduced functional leucocytes activity, plasma concentration of von Willebrand protein and intercellular adhesive molecules. The reduction in collagen III synthesis activity in enalapril therapy was proved. A significant regress of left ventricle hypertrophy due to enalapril treatment was related with favorable non-hemodynamic effects. Conclusion. The research revealed that the blockage of tissue rennin-angiotensin system is very important in prevention of cardiovascular complications especially in high risk patients.